(untitled) (Pedagogy of Higher and Secondary Education, 2013)
Diakonov H. V. Dialogic concept of human-cultural education in psychology and teachers’training faculty. In the article analysed and grounded dialogical approach to the conception of humanitarian-cultural education on a psychological-pedagogical faculty. Grounds, principles, aspects and prospects of development and introduction of this conception in practice of professional preparation of future practical psychologists and social teachers, open up.